The drug-dependent pregnant woman: therapeutic and ethical reflections - Pozzi, Gino; Conte, Gianluigi (Medicina e Morale, 1987)
In our approach the drug addict is considered essentially a sick person, with his own clinical specificity, both somatic and, above all, psychic. In dealing with the drug problem we believe that the 'independent variable' is not the drug, but the person who uses it; and that this must be leveraged to solve the problem.